ISOFLAVON KEDELAI DAN POTENSINYA SEBAGAI PENANGKAP RADIKAL BEBAS - Sussi Astuti (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2008)
Improving of antioxidant status can be achieved by consuming antioxidant containing-food. Consumption of natural food that contains antioxidant will give positive effects for health if it is consumed according to regular on optimum and effective dosage. Isoflavones are the active compound in soybean. By measuring immunohistochemical technique, it was proven increasing the profile of copper, zinc-superoxide dismutase (Cu,Zn-SOD) in the liver, kidney and testis of rats that were given isoflavones by oral administration. As phenolic antioxidants, isoflavones have a potential role for protection of cells in those tissues because of the capability of isoflavone as scavenger free radicals. Keywords: antioxidant, free radical, isoflavone, soybean